Aktivitas Penerbangan dan Perkembangan Populasi Thrips parvispinus Karny (Thysanoptera: Thripidae) pada Tanaman Cabai Besar (Capsicum annuum L.) - PRATIWI, NI PUTU EKA; SUPARTHA, I WAYAN; YULIADHI, KETUT AYU (Agrotrop : Journal on Agriculture Science, 2018)
Flight Activities and Population Development of Thrips parvispinus Karny (Thysanoptera: Thripidae) on Chili (Capsicum annuum L.). Thrips parvispinus Karny (Thysanoptera: Thripidae) is one of the main pests on chili. T. parvispinus attacked the leaves and flowers on chili. The behavior of its attacked fluctuate between morning until late afternoon since the plants grow in the field. The purpose of this research was to know the flight activity of T. parvispinus and its population development on leaf and flower of chilli plant. The research used survey method with direct observation on plants in the field. Flight activity of T. parvispinus was measured by using a yellow sticky trap placed diagonally on the plant. The results showed that daily flight activity of adult T. parvispinus fluctuated between morning, afternoon, and evening. The highest flight activity of adult occurred at 09.00-10.00 (39.81 adults) and the lowest was at 18.00-19.00 (9.84 adults). The population of T. parvispinus nymph was more than adult in the leaf. The highest population of nymphs occurred at 12.00-13.00 (21.07 nymphs). While the population of T. parvispinus adul was more on flower than nymph population. The highest adult population occurred at 18.00-19.00 (27.36 adults). There were strong indications that the nymph stadium frevers live on the part of the leaf than the flower, while the adult prefers the flower rather than the leaf.